Thyroid Diseases in Omani Type 2 Diabetics: A Retrospective Cross-Sectional Study. (17th December 2015) - Al-Sumry, Sanaa; Al-Ghelani, Thuraya; Al-Badi, Huda; Al-Azri, Mohammed; Elshafie, Kawther
Abstract : Background . Diabetes mellitus and thyroid diseases are common endocrine disorders in the general population and found to exist simultaneously. This study aimed to establish the prevalence of thyroid dysfunction among Omani type 2 diabetics and its association with glycemic control. Methodology . A retrospective cross-sectional randomized primary and secondary care based study of 285 Omani type 2 diabetics, ≥ 30 years of age with known thyroid function. The following parameters were examined: age, sex, duration of diabetes, duration of thyroid disease, thyroid morphology, thyroid function, thyroid antibodies, and the mean glycated hemoglobin (mean HbA1C). The prevalence of thyroid dysfunction was compared to an independent control group of randomly selected healthy individuals with known thyroid function. Results . Thyroid dysfunction was found in 12.6% of the diabetic patients compared to 4.9% in the control group. The prevalence was higher among the diabetic females (86%) compared to diabetic males (14%). The commonest thyroid dysfunction among diabetics was overt hypothyroidism (4.6%). Subclinical hypothyroidism was the commonest thyroid dysfunction seen in less controlled diabetics at a mean HbA1c of 7.8 (± 0.7). Conclusion . Screening for thyroid dysfunction in patients with type 2 diabetes mellitus should be routinely performed considering the higher prevalence of thyroid diseases in this group compared to the general population.